Transformational-Generative in Class X Senior High Shcool Arabic Book - Muhammad Agil Munawwar; Wahyu Retno Ningsih; Abdul Wahab Rasyidi (Universitas Ahmad Dahlan, 2023)
There are several cases that occur in Class X, namely: 1) many students do not understand grammar because of the lack of explanation in detail and detail presented in the learning Book, 2) because the lack of presentation of grammar in the textbook reduces the value of the quantity of the textbook. The method used in this study is a literature study, using qualitative descriptive method. The research Data consisted of four aspects, namely book Language, Language skills, vocabulary learning, and sharaf learning aspects. The source of the data in the form of Arabic textbook entitled Arabic student book Scientific Approach curriculum 2013 X Madrasah Aliyah and works sourced from articles about transformative generative theory with data in the form of analysis based on the text read in the book. The purpose of this study was to analyze the Arabic book Madrasah Aliyah Class X with the approach of generative theory Transformative Noam Chomsky. The results showed that class X Arabic textbooks viewed from the view of Noam Chomsky lack of entry in the language order because the arrangement in the textbook has not paid much attention to the side of the language order, so that students ' understanding of the words/sentences presented are still poorly understood. So, it is necessary to add a more detailed and detailed explanation of the grammatical structure that will make it easier for students to learn Arabic well.